Breast reconstruction using the Latissimus Dorsi Flap and Immediate Fat Transfer (LIFT): A systematic review and meta-analysis. Issue 11 (November 2022) - Escandón, Joseph M.; Escandón, Lauren; Ahmed, Aabra; Weiss, Anna; Nazerali, Rahim; Ciudad, Pedro; Langstein, Howard N.; Manrique, Oscar J.
Summary: Background: Despite several efforts have been made to increase the volume of the latissimus dorsi (LD) flap, few studies have reported the outcomes of LD flap and immediate fat transfer (LIFT) to restore a natural native breast appearance during the initial reconstructive procedure. The aim of this study was to report the different surgical techniques used when implementing LIFT for breast reconstruction and evaluate the postoperative outcomes. Methods: A systematic search was conducted across PubMed, Embase, Web of Science, Ovid MEDLINE®, and Scopus. We included articles reporting postoperative outcomes of patients who underwent breast reconstruction with LIFT. Results: We included nineteen studies reporting outcomes of 704 breast reconstructions with LIFT (57.09%). The average age and BMI of patients were 51 years and 26.01 kg/m 2 . The pooled rate of patients requiring additional fat grafting following LIFT was 64.9% (95% CI 43.3%-86.5%). The overall pooled incidence of total flap loss was 3% (95% CI <0%-7.2%), wound-related complications was 14.5% (95% CI 7.3%-21.7%), seroma was 18.2% (95% CI 5.1%-31.2%), and fat necrosis was 14.5% (95% CI 4.5%-24.4%). When compared with abdominal free flaps, we found a significantly lower risk difference of developing wound-related complications favoring LIFT (RD, 0.066; 95%CI 0.004–0.129; p  = 0.038). Conclusions: LIFT offers a totally autologous, less morbid type of reconstruction in breast cancer patients who are not ideal candidates for reconstruction with free tissue transfer. However, immediate fat transfer during reconstruction with the LD flap does not eliminate the need for further fat grafting.